Endogenous Hydrogen Sulfide Is an Important Factor in Maintaining Arterial Oxygen Saturation - Huang, Yan; Wang, Gang; Zhou, Zhan; Tang, Zhengshan; Zhang, Ningning; Zhu, Xiaoyan; Ni, Xin (Frontiers in Pharmacology, 2021)
The gasotransmitter H2S is involved in various physiological and pathophysiological processes. The aim of this study was to investigate the physiological functions of H2S in the lungs. In the model of mouse with genetic deficiency in a H2S natural synthesis enzyme cystathionine-γ-lyase (CSE), we found that arterial oxygen saturation (SaO2) was decreased compared with wild type mice. Hypoxyprobe test showed that mild hypoxia occurred in the tissues of heart, lungs and kidneys in Cse-/- mice. H2S donor GYY4137 treatment increased SaO2 and ameliorated hypoxia state in cardiac and renal tissues. Further, we revealed that lung blood perfusion and airway responsiveness were not linked to reduced SaO2 level. Lung injury was found in Cse-/- mice as evidenced by alveolar wall thickening, diffuse interstitial edema and leukocyte infiltration in pulmonary tissues. IL-8, IL-1β, and TNF-α levels were markedly increased and oxidative stress levels were also significantly higher with increased levels of the pro-oxidative biomarker, MDA, decreased levels of the anti-oxidative biomarkers, T-AOC and GSH/GSSG, and reduced superoxide dismutase (SOD) activity in lung tissues of Cse-/- mice compared with those of wild type mice. GYY4137 treatment ameliorated lung injury and suppressed inflammatory state and oxidative stress in lung tissues of Cse-/- mice. A decrease in SaO2 was found in normal mice under hypoxia. These mice displayed lung injury as evidenced by alveolar wall thickening, interstitial edema and leukocyte infiltration. Increased levels of inflammatory cytokines and oxidative stress were also found in lung tissues of the mice with hypoxia insult. GYY4137 treatment increased SaO2 and ameliorated lung injury, inflammation and oxidative stress. Our data indicate that endogenous H2S is an important factor in maintaining normal SaO2 by preventing oxidative stress and inflammation in the lungs.